RNA Interference-Mediated Knockdown of Male Fertility Genes in the Queensland Fruit Fly Bactrocera tryoni (Diptera: Tephritidae) - Carlos Cruz; Alison Tayler; Steve Whyard (Insects, 2018)
The Queensland fruit fly, Bactrocera tryoni, is Australia’s most important horticultural pest. The Sterile Insect Technique (SIT) has been used to control this species for decades, using radiation to sterilize males before field-release. This method of sterilization can potentially reduce the insects’ abilities to compete for mates. In this study, RNA interference (RNAi) techniques were examined for their potential to sterilize male B. tryoni without adversely affecting mating competitiveness. B. tryoni adults were injected or fed double-stranded RNAs (dsRNAs) targeting spermatogenesis genes (tssk1, topi and trxt); quantitative reverse-transcriptase PCR analyses confirmed that transcript levels were reduced 60–80% for all three genes following injections. Feeding produced a significant gene knockdown for tssk1 and trxt after three days, but interestingly, two genes (trxt and topi) produced an excess of transcripts after 10 days of feeding. Despite these fluctuations in transcript levels, all three dsRNAs impacted the fecundity of treated males, with tssk1- and topi-dsRNA-treated males producing 75% fewer viable offspring than the negative controls. Mating competition assays demonstrated that dsRNA-treated males can actively compete with untreated males. These findings suggest that RNAi technology could serve as an alternative to radiation as a means of sterilizing these insects in an SIT program.